2022
DOI: 10.1186/s12875-022-01814-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a mHealth-based integrated hospital-community-home program for people with type 2 diabetes in transitional care: a protocol for a multicenter pragmatic randomized controlled trial

Abstract: Background Diabetes is a progressive condition requiring long-term medical care and self-management. The ineffective transition from hospital to community or home health care may result in poor glycemic control and increase the risk of serious diabetes-related complications. In China, the most common transitional care model is home visits or telephone interventions led by a single healthcare setting, with a lack of cooperation between specialists and primary care, which leads to inadequate serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The Hospital-Community-Home (HCH) model, serving as a continuum of care, aims to facilitate a seamless transition for patients from hospital settings to community or home environments while ensuring specialized care ( 6 ). In recent years, this care model has gained significant recognition for its ability to meet the ongoing healthcare needs of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The Hospital-Community-Home (HCH) model, serving as a continuum of care, aims to facilitate a seamless transition for patients from hospital settings to community or home environments while ensuring specialized care ( 6 ). In recent years, this care model has gained significant recognition for its ability to meet the ongoing healthcare needs of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigated the effectiveness of a mHealth intervention on medication adherence in patients with T2DM. The study found that the intervention effectively improved medication adherence and glycemic control in patients with poor adherence at baseline [ 11 ].…”
Section: Introductionmentioning
confidence: 99%